Sliding member, bearing, method for manufacturing sliding member, method for manufacturing bearing

By introducing matrix phases of Cu and Sn and hard particles of Lavers phase of Co, Mo, and Si into the sliding layer of the lead bronze sintered bearing alloy, the problems of wear and thermal viscosity in high-speed and high-load environments are solved. Achieved higher wear resistance and hot tack resistance.

CN116710219BActive Publication Date: 2025-01-21SENJU METAL IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180086832.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-25
Filing Date
2021-11-01
Publication Date
2025-01-21
Estimated Expiration
2041-11-01

AI Technical Summary

Technical Problem

In the use environment of high-speed and high-loading, the wear and thermal viscosity of lead-bronze-based sintered bearing alloys are more prominent, and it is difficult to obtain sufficient lubrication.

Method used

Using a sliding layer with a matrix phase of Cu and Sn and hard particles of the Lavers phase composed of Co, Mo and Si, the sliding layer is formed by spreading mixed powder on the metal substrate and sintering at 800 to 900°C to improve friction. properties and wear resistance.

Benefits of technology

It achieves better wear resistance and hot viscosity resistance than traditional LBC3 bearings, reduces friction and wear, and increases the service life of the bearing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116710219B_ABST
    Figure CN116710219B_ABST
Patent Text Reader

Abstract

The sliding member comprises a metal substrate and a sliding layer formed on one surface of the metal substrate. The sliding layer has a matrix phase containing Cu and Sn and hard particles dispersed in the matrix phase, wherein the hard particles contain a Laves phase composed of Co, Mo and Si.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a sliding member, a bearing, a method for manufacturing a sliding member, and a method for manufacturing a bearing. Background Art

[0002] Lead bronze sintered bearing alloys are widely used as sliding component materials for automobiles and general industrial machinery. The main components of lead bronze are Cu, Sn, and Pb. As copper alloy castings, they are specified by JIS H5120, etc. Among them, for the copper alloy specified as CAC603 (hereinafter referred to as LBC3), medium-high speed / high load bearings, large engine bearings, etc. can be listed as uses. The copper alloy contains about 10% lead by mass as a solid lubricant and plays the role of improving the friction characteristics. Lead, as a soft metal, is prone to plastic deformation, thereby acting as a lubricant between the two friction surfaces, resulting in a material with excellent friction characteristics.

[0003] However, LBC3, which is a general-purpose product, suffers from significant wear and seizure in a usage environment such as boundary lubrication where sufficient lubrication is not obtained due to the increase in speed and load in the usage environment, and improvement thereof has become a problem.

[0004] Japanese Patent Application Laid-Open Nos. 2008-50688 and 2005-163074 propose copper-based sliding materials that are Cu-Sn-Bi alloys containing Cu as a main component and Sn and Bi added to a Cu base as lead-free sliding materials. Summary of the invention

[0005] It is desirable to provide a sliding member and a bearing that are improved in wear resistance compared to LBC3.

[0006] A sliding component according to one embodiment includes a metal substrate and a sliding layer formed on one surface of the metal substrate, wherein the sliding layer has: a matrix phase containing Cu and Sn; and hard particles dispersed in the matrix phase, wherein the hard particles contain a Laves phase composed of Co, Mo and Si. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 This is a longitudinal sectional view showing a schematic structure of a sliding member according to one embodiment.

[0008] Figure 2 This is an optical microscope photograph of a cross-sectional structure of a sliding layer of a sliding member according to one embodiment.

[0009] Figure 3 This is a mapping image obtained by EPMA of the cross-sectional structure of the sliding layer of the sliding member according to one embodiment.

[0010] Figure 4 This is a mapping image obtained by EPMA of a hard particle portion in a cross-sectional structure of a sliding layer of a sliding member according to one embodiment.

[0011] Figure 5 It is a perspective view showing a schematic structure of a bearing according to one embodiment.

[0012] Figure 6 It is a figure which shows the manufacturing process of the sliding member which concerns on one Embodiment.

[0013] Figure 7 It is a figure which shows the outline of a friction and wear test.

[0014] Figure 8 It is a figure which shows the outline of a shearing processing test. DETAILED DESCRIPTION

[0015] In this specification, unless otherwise specified, "%" about the composition means "mass %". In addition, in this specification, unless otherwise specified, "○○~△△" (○○, △△ are both numbers) means "above ○○ and below △△". In addition, in this specification, "main component" means a component containing 50% by mass or more relative to the whole composition. In addition, in this specification, "hard particle powder" refers to the powder before sintering, and "hard particles" refer to the particles in the sliding layer after sintering. As described later, Cu and Sn contained in the hard particle powder migrate to the matrix to a certain extent during sintering, so the content of hard particles in the sliding layer changes from the amount of hard particle powder in the mixed powder, and the content of each constituent element in the hard particles is different from the content of each constituent element in the hard particle powder (the hard particles are particles of a composition in which the content of Sn and Cu in the chemical composition is reduced to a certain extent compared with the hard particle powder).

[0016] The sliding component of the first embodiment comprises: a metal substrate and a sliding layer formed on one surface of the metal substrate, the sliding layer having: a matrix phase containing Cu and Sn; and hard particles dispersed in the matrix phase, the hard particles containing a Laves phase composed of Co, Mo and Si.

[0017] A sliding member according to a second aspect of the embodiment is the sliding member according to the first aspect, wherein the sliding layer further includes a compound phase dispersed in the matrix phase, the compound phase containing Co, Fe, Ni, Si, and Cr.

[0018] A sliding member according to a third aspect of the embodiment is the sliding member according to the second aspect, wherein the sliding layer further includes Bi particles dispersed in the matrix phase.

[0019] A sliding member according to a fourth aspect of an embodiment is the sliding member according to any one of the first to third aspects, wherein the content of the hard particles is 40% by mass or less when the entire sliding layer is 100% by mass.

[0020] A bearing according to a fifth aspect of the embodiment includes a metal substrate and a sliding layer formed on one surface of the metal substrate.

[0021] The sliding layer is used as the inner side to form a ring shape, and the inner peripheral surface of the cylindrical shape is composed of the sliding layer.

[0022] In the above bearings,

[0023] The above sliding layer has:

[0024] a matrix phase comprising Cu and Sn; and

[0025] The hard particles dispersed in the matrix phase contain a Laves phase composed of Co, Mo and Si.

[0026] A method for manufacturing a sliding member according to a sixth aspect of the embodiment includes:

[0027] A step of spreading a mixed powder having a first powder containing Cu, Sn and Bi and a hard particle powder containing a Laves phase composed of a composition of Co, Mo and Si on one surface of a metal substrate, wherein the mixed powder contains Cu, Si, Fe, Mo, Co and Cr; and

[0028] The mixed powder dispersed on the metal substrate is sintered at 800-900°C.

[0029] A method for producing a sliding member according to a seventh aspect of the embodiment is the method for producing a sliding member according to the sixth aspect, wherein the hard particle powder further contains Sn.

[0030] A method for producing a sliding member according to an eighth aspect of an embodiment is the method for producing a sliding member according to the seventh aspect, wherein the hard particle powder contains 1 mass % or more of Sn.

[0031] A ninth aspect of the present invention is a method for manufacturing a sliding member according to any one of the sixth to eighth aspects, wherein the amount of the hard particle powder blended is 1 to 40% by mass when the entire mixed powder is 100% by mass.

[0032] A method for manufacturing a sliding member according to a tenth aspect of an embodiment is a method for manufacturing a sliding member according to any one of the sixth to ninth aspects, wherein the mixed powder further includes a second powder containing Cu, Co, Fe, Ni, Si, and Cr.

[0033] The method for manufacturing a sliding member according to an eleventh aspect of the embodiment is the method for manufacturing a sliding member according to the tenth aspect, wherein the second powder further contains Sn.

[0034] A method for manufacturing a sliding member according to a twelfth aspect of an embodiment is the method for manufacturing a sliding member according to the eleventh aspect, wherein the second powder contains 1 mass % or more of Sn.

[0035] A thirteenth aspect of the embodiment is a method for manufacturing a sliding member according to any one of the tenth to twelfth aspects, wherein the blending amount of the second powder is 2 to 38 mass % when the entire mixed powder is 100 mass %.

[0036] The manufacturing method of a sliding component of the 14th embodiment is a manufacturing method of a sliding component according to any one of the 10th to 13th embodiments, wherein, when the above-mentioned mixed powder as a whole is set to 100 mass%, the blending amount of the above-mentioned hard particle powder is 1 to 40 mass%, and the blending amount of the above-mentioned second powder is 2 to 38 mass%.

[0037] A method for producing a sliding member according to a fifteenth aspect of an embodiment is the method for producing a sliding member according to any one of the sixth to fourteenth aspects, wherein the first powder further contains P.

[0038] The manufacturing method of a sliding component of the 16th embodiment is a manufacturing method of a sliding component according to any one of the 6th to 15th embodiments, wherein, when the hard particle powder as a whole is set to 100 mass%, the content of each constituent element in the above-mentioned hard particle powder is Si: 3 to 7 mass%, Fe: 2 to 16 mass%, Mo: 24 to 28 mass%, Co: 14 to 20 mass%, Cr: 1 to 10 mass%, Sn: 1 to 15 mass%, and Cu: balance.

[0039] The manufacturing method of a sliding component of the 17th embodiment is a manufacturing method of a sliding component according to any one of the 10th to 14th embodiments, wherein, when the second powder as a whole is set to 100 mass%, the content of each constituent element in the above-mentioned second powder is Co: 0.6~4.6 mass%, Fe: 1.6~5.6 mass%, Ni: 10~14 mass%, Si: 0.5~4.5 mass%, Cr: 0.5~1.5 mass%, Sn: 1~15 mass%, Cu: balance.

[0040] A bearing manufacturing method according to an eighteenth aspect of the embodiment includes:

[0041] A step of spreading a mixed powder on one surface of a metal substrate, the mixed powder comprising a first powder containing Cu, Sn and Bi and a hard particle powder containing a Laves phase composed of a composition of Co, Mo and Si, the hard particle powder containing Cu, Si, Fe, Mo, Co and Cr;

[0042] The step of sintering the mixed powder dispersed on the metal substrate at 800-900° C. to form a sliding layer;

[0043] A step of rolling the metal substrate on which the sliding layer is formed; and

[0044] A step of processing the rolled metal base material into a rolled bushing shape with the sliding layer as the inner side.

[0045] The manufacturing method of a bearing of the 19th embodiment is a manufacturing method of a bearing according to the 18th embodiment, wherein, when the hard particle powder as a whole is set to 100 mass%, the content of each constituent element in the above-mentioned hard particle powder is Si: 3~7 mass%, Fe: 2~16 mass%, Mo: 24~28 mass%, Co: 14~20 mass%, Cr: 1~10 mass%, Sn: 1~15 mass%, Cu: balance.

[0046] A bearing manufacturing method according to a 20th aspect of the embodiment is the bearing manufacturing method according to the 18th or 19th aspect, wherein the mixed powder further includes a second powder containing Cu, Co, Fe, Ni, Si, and Cr.

[0047] The manufacturing method of a bearing of the 21st embodiment is based on the manufacturing method of a bearing of the 20th embodiment, wherein, when the second powder as a whole is set to 100 mass%, the content of each constituent element in the above-mentioned second powder is Co: 0.6~4.6 mass%, Fe: 1.6~5.6 mass%, Ni: 10~14 mass%, Si: 0.5~4.5 mass%, Cr: 0.5~1.5 mass%, Sn: 1~15 mass%, Cu: balance.

[0048] The mixed powder according to the 22nd aspect of the embodiment includes:

[0049] a first powder comprising Cu and Sn;

[0050] A hard particle powder containing a Laves phase composed of Co, Mo, and Si and further containing 1 mass % or more of Sn; and

[0051] A second powder containing Cu, Co, Fe, Ni, Si, and Cr, and further containing 1 mass % or more of Sn.

[0052] The mixed powder of the 23rd embodiment is a mixed powder according to the 22nd embodiment, wherein, when the hard particle powder as a whole is set to 100 mass%, the content of each constituent element in the above-mentioned hard particle powder is Si: 3~7 mass%, Fe: 2~16 mass%, Mo: 24~28 mass%, Co: 14~20 mass%, Cr: 1~10 mass%, Sn: 1~15 mass%, Cu: balance.

[0053] The mixed powder of the 24th embodiment is a mixed powder according to the 22nd or 23rd embodiment, wherein, when the second powder as a whole is set to 100 mass%, the content of each constituent element in the above-mentioned second powder is Co: 0.6~4.6 mass%, Fe: 1.6~5.6 mass%, Ni: 10~14 mass%, Si: 0.5~4.5 mass%, Cr: 0.5~1.5 mass%, Sn: 1~15 mass%, Cu: balance.

[0054] The hard particle powder for bearings according to the twenty-fifth aspect of the embodiment contains a Laves phase composed of Co, Mo, and Si, and further contains 1 mass % or more of Sn.

[0055] The 26th embodiment of the hard particle powder for bearings is a hard particle powder for bearings according to the 25th embodiment, wherein, when the hard particle powder as a whole is set to 100 mass%, the content of each constituent element in the above-mentioned hard particle powder for bearings is Si: 3~7 mass%, Fe: 2~16 mass%, Mo: 24~28 mass%, Co: 14~20 mass%, Cr: 1~10 mass%, Sn: 1~15 mass%, Cu: balance.

[0056] The bearing powder according to the twenty-seventh aspect of the embodiment contains Cu, Co, Fe, Ni, Si, and Cr, and further contains 1 mass % or more of Sn.

[0057] The bearing powder of the 28th embodiment is a bearing powder according to the 27th embodiment, wherein, when the entire powder is set to 100 mass%, the content of each constituent element in the above-mentioned bearing powder is Co: 0.6~4.6 mass%, Fe: 1.6~5.6 mass%, Ni: 10~14 mass%, Si: 0.5~4.5 mass%, Cr: 0.5~1.5 mass%, Sn: 1~15 mass%, Cu: balance.

[0058] The hard particle powder of the 29th embodiment of the implementation method contains a Laves phase composed of Co, Mo and Si. When the entire hard particle powder is set to 100 mass%, Co: 14-20 mass%, Mo: 24-28 mass%, Si: 3-7 mass%, Fe: 2-16 mass%, Cr: 1-10 mass%, Sn: 4 mass% or more, Cu: balance.

[0059] Hereinafter, specific examples of the embodiments will be described in detail with reference to the accompanying drawings. It should be noted that in the following description and the accompanying drawings used in the following description, the same reference numerals are used for parts that can have the same configuration, and repeated descriptions are omitted.

[0060] <Structure of sliding member>

[0061] Figure 1 1 is a longitudinal sectional view showing a schematic structure of a sliding member 1 according to an embodiment. Figure 1 As shown, the sliding member 1 includes a metal substrate 2 and a sliding layer 3 formed on one surface, that is, the surface of the metal substrate 2 .

[0062] The material of the metal substrate 2 is not particularly limited as long as it has the strength and shape stability to be used as a bearing backing base material. For example, it can be low-carbon steel (SPCC, SS400, etc.) or a copper-plated steel plate with Cu plated on an Fe-based plate.

[0063] The sliding layer 3 is formed by sintering metal powder (mixed powder described later) on the surface of the metal substrate 2. The thickness of the sliding layer 3 can be, for example, 0.3 mm or less. Figure 2 This is an optical microscope photograph of the cross-sectional structure of the sliding layer 3 obtained by etching with ferric chloride. Figure 3 This is a mapping image of the cross-sectional structure of the sliding layer 3 obtained by an electron probe microanalyzer (EPMA).

[0064] like Figure 2 and Figure 3 As shown, the sliding layer 3 has a matrix phase 10 containing Cu and Sn and hard particles 11 dispersed in the matrix phase 10 .

[0065] Among them, the matrix phase 10 is a bronze alloy containing Cu as a main component and further containing Sn. Figure 3 As shown, the matrix phase 10 may be composed of a solid solution of Cu, Sn, and Ni.

[0066] like Figure 2 and Figure 3 As shown, Bi particles can be distributed in the grain boundaries of the matrix phase 10. In this case, Bi exhibits the same self-lubricating effect as Pb in conventional lead bronze, and acts as a lubricant between two frictional surfaces, thereby achieving friction reduction.

[0067] Figure 4 This is a mapping image of the hard particles 11 in the cross-sectional structure of the sliding layer 3 obtained by EPMA. Figure 4As shown, the hard particles 11 contain a Laves phase composed of Co, Mo and Si. Here, the Laves phase is an AB2 type intermetallic compound composed of an A element and a B element with an atomic radius ratio of about 1.2:1. There are three types of structures: MgZn2 (C14) type, MgCu2 (C15) type, and MgNi2 (C36) type. The Laves phase composed of Co, Mo and Si (more specifically, Co3Mo2Si) is a Laves phase in which the A element is Mo, the B element is Co, and 25 atomic % of Co is replaced by Si. It is a MgZn2 type with a hexagonal crystal structure. The Vickers hardness of the Laves phase composed of Co3Mo2Si is Hv1000~1200.

[0068] like Figure 2 and Figure 3 As shown, the hard particles 11 are distributed in the grain boundaries of the matrix phase 10. It is believed that the hard particles 11 dispersed in the matrix phase 10 can bear a higher load than the soft bronze as the matrix phase 10, and the hard Laves phase composed of Co, Mo and Si precipitates on the friction surface to support the load, thereby being able to advantageously act to reduce the wear of the sliding layer 3.

[0069] In addition, in the present embodiment, a sulfide film of MoS2 can be formed on the friction surface by Mo in the Laves phase and S in the lubricating oil. MoS2 is a sulfide material known as a solid lubricant that replaces lead and helps improve friction characteristics. Compared with the bonds between molybdenum and between molybdenum and sulfur, the bonds between sulfurs are weaker. Therefore, if friction occurs, the bonds between sulfurs are selectively cut, thereby generating lubrication, which can effectively contribute to the suppression of wear. In addition, the Mo oxide generated on the friction surface due to the oxidation of Mo in the Laves phase during sliding also exerts a lubricating effect, which can effectively contribute to the suppression of wear.

[0070] When the sliding layer 3 as a whole is set to 100 mass%, the content of the hard particles 11 can be, for example, 40 mass% or less. When the sliding layer 3 as a whole is set to 100 mass%, the content of the hard particles 11 can be, for example, 0.1 mass% or more. When the content of the hard particles 11 is 0.1 mass% or more, the wear reduction effect of the sliding layer 3 as described above can be obtained. In addition, when the sliding layer 3 as a whole is set to 100 mass%, the content of the Laves phase composed of the composition of Co, Mo and Si can be, for example, 0.1 to 20 mass%.

[0071] like Figure 2 and Figure 3 As shown, the sliding layer 3 may also have a compound phase 12 dispersed in the matrix phase 10 .

[0072] The compound phase 12 contains Co, Fe, Ni, Si, and Cr. By forming the compound phase 12 in the matrix phase 10, the hardness of the matrix phase 10 can be increased, which can advantageously contribute to the improvement of hot seizure resistance.

[0073] <Bearing structure>

[0074] Next, the structure of the bearing 20 according to one embodiment will be described. Figure 5 FIG. 2 is a perspective view showing a schematic structure of a bearing 20 according to an embodiment. Figure 5 As shown, the bearing 20 is, for example, a sliding bearing, and the sliding member 1 having the above structure is formed into an annular shape with the sliding layer 3 as the inner side. The bearing 20 supports a shaft 21 as a sliding object by the sliding layer 3 forming a cylindrical inner peripheral surface.

[0075] The bearing 20 can be applied to either the rotational motion or linear motion of the shaft 21. The bearing 20 can be used, for example, in a sliding part that uses oil in a linear motion, such as a shock absorber of an automobile. In addition, the bearing 20 can also be used in a sliding part that uses oil in a rotational motion, such as a gear pump that delivers oil by rotating a gear-shaped member. In addition, as another form of the bearing of this embodiment, a rolling bearing used in a transmission can also be cited.

[0076] <Method for manufacturing sliding member and bearing>

[0077] Next, refer to Figure 6 , a method for manufacturing the sliding member 1 and the bearing 20 according to the present embodiment will be described. Figure 6 It is a figure which shows the manufacturing process of the sliding member 1.

[0078] like Figure 6 As shown, first, a first powder containing Cu and Sn and a hard particle powder containing a Laves phase composed of Co, Mo and Si are mixed to produce a mixed powder (step S10). A second powder containing Cu, Co, Fe, Ni, Si and Cr may also be mixed with the first powder and the hard particle powder to produce a mixed powder.

[0079] Here, the first powder is a bronze alloy powder containing Cu as a main component and further containing Sn. The first powder may further contain Bi or P. When the first powder contains Bi, Bi particles are precipitated in the matrix phase 10 during the sintering of the mixed powder described later (i.e., step S12), and Bi exhibits the same self-lubricating effect as Pb of conventional lead bronze, so that low friction can be achieved. In addition, when the first powder contains P, it is possible to remove oxygen mixed in copper (deoxidation) and suppress hydrogen embrittlement. The content of each constituent element of the first powder may be Sn: 10 to 11 mass%, Cu: the balance. When Bi is also contained, Bi: 7 to 9 mass% is preferred, and when P is contained, P: 0.02 mass% or less is preferred. The amount of the first powder in the mixed powder is the amount of the remainder after deducting the total amount of powders other than the first powder from the amount of the entire mixed powder.

[0080] The hard particle powder is an alloy powder containing a Laves phase composed of Co, Mo and Si and Cu, that is, a hard particle powder containing Cu, Si, Fe, Mo, Co and Cr. The hard particle powder may also contain Sn, for example, it may contain more than 1% by mass of Sn, or it may contain more than 4% by mass of Sn. The solid phase temperature of the hard particle powder without Sn reaches nearly 1450°C, but by containing Sn, the solid phase temperature of the hard particle powder can be lowered, and the hard particle powder can be solid-phase sintered to the tile back base material at nearly 800°C. In addition, the Sn contained in the hard particle powder dissolves into the Cu-Sn matrix phase 10 side of the first powder during sintering and diffuses and bonds. By causing sintering to proceed due to the shrinkage of Sn powder, solid solution strengthening caused by Sn in the matrix phase 10 and Sn contained in the hard particle powder can be demonstrated. When the hard particle powder as a whole is set to 100 mass%, the content of each constituent element in the hard particle powder can be Co: 14-20 mass%, Mo: 24-28 mass%, Si: 3-7 mass%, Fe: 2-16 mass%, Cr: 1-10 mass%, Cu: balance. In the case of containing Sn, when the hard particle powder as a whole is set to 100 mass%, the content of each constituent element in the hard particle powder can be Co: 14-20 mass%, Mo: 24-28 mass%, Si: 3-7 mass%, Fe: 2-16 mass%, Cr: 1-10 mass%, Sn: 1-15 mass%, Cu: balance. When the mixed powder as a whole is set to 100 mass% (that is, when the sliding layer 3 as a whole is set to 100 mass%), the blending amount of the hard particle powder can be 1-40 mass%, preferably 1-3 mass%. Since Cu and Sn are dissolved from the hard particle powder during sintering, the content of the hard particles 11 in the sliding layer 3 varies from the blending amount of the hard particle powder in the mixed powder.

[0081] The second powder is an alloy powder containing Cu as a main component and also containing Co, Fe, Ni, Si and Cr. The second powder may also contain Sn, for example, it may contain more than 1 mass% Sn, or it may contain more than 4 mass% Sn. The solidus temperature of the second powder without Sn reaches close to 1240°C, but by containing Sn, the solidus temperature of the second powder can be lowered, and the second powder can be solid-phase sintered to the tile back base material at close to 800°C. In the case of containing Sn, when the second powder as a whole is set to 100 mass%, the content of each constituent element in the second powder can be Co: 0.6~4.6 mass%, Fe: 1.6~5.6 mass%, Ni: 10~14 mass%, Si: 0.5~4.5 mass%, Cr: 0.5~1.5 mass%, Sn: 1~15 mass%, Cu: balance. When the mixed powder contains the second powder, the blending amount of the second powder may be 2 to 38 mass %, preferably 10 to 38 mass %, and more preferably 17 to 19 mass %, based on 100 mass % of the entire mixed powder.

[0082] When the entire mixed powder is 100 mass %, the blending amount of the hard particle powder may be 1 to 40 mass %, and the blending amount of the second powder may be 15 to 18 mass %. In this case, excellent shear workability can be achieved.

[0083] The first powder, the hard particle powder, and the second powder can be produced by spraying by a gas atomization method, for example. In the gas atomization method, the heat source for melting can be high frequency, and the crucible (with a nozzle at the bottom) can be made of zirconia.

[0084] The particle size of the first powder can be, for example, 45 μm to 180 μm. The particle size of the hard particle powder can be, for example, 53 μm to 180 μm. The particle size of the second powder can be 53 μm to 150 μm. Here, "particle size" refers to the particle size distribution measured by the laser diffraction / scattering method using the particle size distribution measuring device MT3300EXII manufactured by Microtrac Bell. This measurement method is a measurement method based on the test step after the process of extracting powder from the paste in the "Laser Diffraction Particle Size Distribution Measurement Test of 4.2.3" of JIS Z3284-2.

[0085] Then, if Figure 6As shown, a mixed powder including a first powder and a hard particle powder is spread on one surface of a metal substrate (step S11). The mixed powder may include a second powder. Then, the mixed powder spread on the metal substrate is sintered at 800-900°C to form a sliding layer (step S12). As described above, the solid phase temperatures of the hard particle powder and the second powder without Sn reach approximately 1450°C and 1240°C, respectively, but by containing Sn, the solid phase temperatures of the hard particle powder and the second powder can be lowered, and the hard particle powder and the second powder can be solid-phase sintered to the metal substrate (tile back parent material) at approximately 800°C. In addition, the Sn contained in the hard particle powder dissolves in the Cu-Sn matrix phase 10 side of the first powder during sintering and diffuses and bonds. By causing sintering to proceed due to the shrinkage of Sn powder, the solid solution strengthening brought about by the Sn in the matrix phase 10 and the Sn contained in the hard particle powder is exhibited, and a high-strength alloy can be formed in the end.

[0086] Then, if Figure 6 As shown, the metal substrate with the sliding layer is rolled (step S13). Thus, the sliding member 1 having the above structure is manufactured (refer to Figure 1 to Figure 4 Then, the rolled metal substrate (sliding member 1) is processed into a rolled bushing shape with the sliding layer as the inner side, thereby manufacturing the bearing 20 having the above structure (refer to Figure 5 ).

[0087] <Example>

[0088] Next, specific examples of this embodiment will be described.

[0089] (Preparation of test pieces)

[0090] The inventors of the present application first prepared samples of the first powder, the hard particle powder, and the second powder by spraying based on the gas atomization method with the mass ratio of the chemical components shown in the following Table 1. That is, the sample of the first powder is composed of 10 mass% Sn, 8 mass% Bi, and the balance of Cu. In addition, the sample of the hard particle powder is composed of 4.5 mass% Sn, 5 mass% Si, 15 mass% Fe, 26 mass% Mo, 16 mass% Co, 4 mass% Cr, and the balance of Cu. In addition, the sample of the second powder is composed of 7.8 mass% Sn, 12 mass% Ni, 2.5 mass% Si, 3.6 mass% Fe, 2.6 mass% Co, 1 mass% Cr, and the balance of Cu. The solidus temperatures of the samples of the first powder, the hard particle powder, and the second powder are 800°C, 790°C, and 883°C, respectively, based on the measurement results of differential scanning calorimetry (DSC).

[0091] [Table 1]

[0092] Table 1: Chemical composition of powder

[0093]

[0094] Next, the test pieces of Examples 1 to 18 and Comparative Example 2 were prepared according to the following steps. That is, the samples of the first powder, the hard particle powder, and the second powder were mixed in the mixing ratio shown in Table 2 below to prepare a mixed powder. Here, the particle size of the sample of the second powder was less than 105 μm, and the sample of the hard particle powder used a powder with a particle size adjusted to 53 μm to 105 μm. These mixed powders were spread on the tile back base material SS400, and sintered under the conditions of a primary sintering temperature of 850°C and a sintering time of 60 minutes. In order to achieve the densification of the sintered structure, the primary rolling rate was 7.7±0.2%. Then, the secondary sintering was performed at 850°C, and the secondary rolling rate was adjusted to 2.9±0.4% to perform rolling in order to complete the alloy thickness of 0.8±0.2 mm, thereby preparing the test pieces of Examples 1 to 18 and Comparative Example 2. Similarly, a test piece of Comparative Example 1 was produced by sintering LBC3 on a tile back base material SS400 and then rolling it.

[0095] [Table 2]

[0096] Table 2: Powder mix ratio

[0097]

[0098] It should be noted that the amount of hard particle powder in the test pieces of Examples 1 to 18 is 1% by mass or more, specifically 2% to 40% by mass, when the entire mixed powder is 100% by mass. This corresponds to a content of hard particles 11 of 40% by mass or less when the entire sliding layer 3 is 100% by mass.

[0099] (Evaluation Test)

[0100] Next, the Vickers hardness of the matrix phase was measured for the test pieces of Examples 1 to 18 and Comparative Example 2. The measurement results are shown in the column of "bronze portion hardness" in Table 3 below. In addition, the friction and wear test and shearing test described below were performed for the test pieces of Examples 1 to 18 and Comparative Examples 1 and 2.

[0101] (a) Friction and wear test

[0102] This evaluation is to compare the hot sticking resistance and wear resistance of the test pieces. It should be noted that this evaluation is an evaluation test in oil, but since there is no gap between the cylindrical ring and the bearing metal, they are in sliding contact in a state of complete contact, so it is actually an evaluation in a boundary lubrication environment where almost no oil film is formed.

[0103] In this review, we used Figure 7 The thrust tester shown. Hydraulic working oil (VG32) was used. The amount of oil in the universal joint container was 250cc, and the counterpart cylindrical ring was SCM435 with an outer diameter of Φ30 and an inner diameter of Φ24. The surface roughness of the counterpart material was Ra 0.04μm, and the surface roughness of the bearing alloy was polished to Ra 0.5μm.

[0104] In the hot-stuck test, the circumferential speed was set to 0.2 m / s and the step load was set to 0.6 MPa / 30 s. The load at the point where the friction coefficient reached 0.5 or the temperature of the back side of the test piece reached 200°C was divided by 254 mm. 2 The value obtained by the friction cross-sectional area is defined as the hot bonding surface pressure. The measurement results are shown in the "Hot Bonding Surface Pressure" column of Table 3 below. In Table 3 below, the test piece with a hot bonding surface pressure of 25 MPa or more is evaluated as "0", and the test piece with a hot bonding surface pressure of less than 25 MPa is evaluated as "×".

[0105] In the wear test, the wear depth after continuous operation for 10 hours under certain conditions of a peripheral speed of 1.0 m / s and a surface pressure of 2.5 MPa was measured, and the specific wear amount (wear amount per unit time) was calculated. The measurement results are shown in the "Specific Wear Amount" column of Table 3 below. In Table 3 below, the test piece with a specific wear amount of less than 0.001 mm / hour was evaluated as "0", and the test piece with a specific wear amount of more than 0.001 mm / hr was evaluated as "×".

[0106] (b) Shearing test

[0107] When the sliding parts are commercialized, it is necessary to process the materials into bushing shapes by processing such as slits and fillets after sintering. Figure 8 The method shown in the figure is to perform shearing (shearing test) from the alloy side (sliding layer side) and observe the state of alloy cracks on the shear surface. Here, the layer thickness of the test piece after secondary rolling is 5.5±0.03mm, and the lining thickness is 0.8±0.2mm. The surface of the sheared part is observed with a microscope, and the fracture surface is observed with an optical microscope.

[0108] [Table 3]

[0109] Table 3: Effect of powder mix ratio on hot sticking resistance

[0110]

[0111] (Results and Investigation)

[0112] Table 3 shows the measurement results of the Vickers hardness, specific wear amount, and hot-stuck surface pressure of the matrix phase portion of the test specimens of Examples 1 to 18 and Comparative Examples 1 and 2.

[0113] The test pieces of Examples 1 to 18 are test pieces in which a sliding layer is formed by sintering a mixed powder containing a first powder and a hard particle powder, that is, hard particles containing a Laves phase composed of a composition of Co, Mo, and Si are dispersed in the sliding layer. The sliding layers of the test pieces of Examples 1 to 18 contain Sn, Bi, Cu, Si, Fe, Mo, Co, and Cr. In addition, Ni is also contained in the sliding layer of the test piece of the embodiment containing the second powder. On the other hand, the test piece of Comparative Example 1 is a test piece in which a sliding layer is formed by sintering LBC3, and the test piece of Comparative Example 2 is a test piece in which a sliding layer is formed by sintering a mixed powder without hard particle powder, and any of the test pieces is a test piece in which hard particles containing a Laves phase composed of a composition of Co, Mo, and Si are not present in the sliding layer.

[0114] As can be seen from Table 3, the evaluation of the specific wear amount of the test pieces of Examples 1 to 18 was "0", while the evaluation of the specific wear amount of the test pieces of Comparative Examples 1 and 2 was "×", and the specific wear amount of the test pieces of Examples 1 to 18 was lower than that of the test pieces of Comparative Examples 1 and 2. It can be said that by making the sliding layer of the sliding member have hard particles containing the Laves phase composed of the composition of Co, Mo and Si, it is possible to achieve better wear resistance than LBC3.

[0115] The test pieces of Examples 1 to 5 have the same blending amount of the hard particle powder but different blending amounts of the second powder, that is, have the same amount of hard particles contained in the sliding layer but different amounts of the compound phase.

[0116] As can be seen from Table 3, in the test pieces of Examples 1 to 5, as the amount of the second powder added increases, the Vickers hardness of the matrix phase increases. In addition, in the test pieces of Examples 4 and 5 in which the amount of the second powder added is less than 10% by mass, the evaluation of heat resistance is "×", while in the test pieces of Examples 1 to 3 in which the amount of the second powder added is 10% by mass or more, the evaluation of heat resistance is "0". It can be said that by making the sliding layer of the sliding member have a compound phase containing Co, Fe, Ni, Si and Cr, the hardness of the matrix phase 10 can be improved. In addition, it can be said that by making the amount of the second powder added be 10% by mass or more, better heat resistance than LBC3 can be achieved.

[0117] In addition, in the above shearing test, the shearing properties of the test pieces of Examples 3 and 13 were good compared with the other test pieces, and it was confirmed that the test piece of Example 3 had particularly few cracks and good processing. It can be said that when the entire mixed powder is 100 mass%, excellent shearing properties can be achieved by setting the blending amount of the hard particle powder to 2-5 mass% and the blending amount of the second powder to 15-18 mass%.

[0118] The embodiments and modifications are described above by way of example, but the technical scope of the present invention is not limited thereto, and changes and modifications can be made according to the purpose within the scope described in the claims. In addition, each embodiment and modification can be appropriately combined within the scope of not contradicting the processing contents.

Claims

1. A sliding member, characterized in that: A metal substrate and a sliding layer formed on one surface of the metal substrate, The sliding layer has: a matrix phase comprising Cu and Sn; and hard particles dispersed in the matrix phase, the hard particles containing a Laves phase composed of Co, Mo and Si, The sliding layer also has a compound phase dispersed in the matrix phase, the compound phase containing Co, Fe, Ni, Si and Cr, The sliding layer further has Bi particles dispersed in the matrix phase.

2. The sliding member according to claim 1, characterized in that When the entire sliding layer is taken as 100 mass %, the content of the hard particles is 40 mass % or less.

3. A bearing, characterized in that: A metal substrate and a sliding layer formed on one surface of the metal substrate, The sliding layer is used as the inner side to form a ring shape, and the inner peripheral surface of the cylindrical shape is composed of the sliding layer. In the bearing, The sliding layer has: a matrix phase comprising Cu and Sn; and hard particles dispersed in the matrix phase, the hard particles containing a Laves phase composed of Co, Mo and Si, The sliding layer also has a compound phase dispersed in the matrix phase, the compound phase containing Co, Fe, Ni, Si and Cr, The sliding layer further has Bi particles dispersed in the matrix phase.

4. A method for manufacturing a sliding member, characterized in that: have: A step of spreading a mixed powder having a first powder containing Cu, Sn and Bi and a hard particle powder containing a Laves phase composed of a composition of Co, Mo and Si on one surface of a metal substrate, wherein the mixed powder contains Cu, Si, Fe, Mo, Co and Cr; and The mixed powder spread on the metal substrate is sintered at 800-900°C.

5. The method for manufacturing a sliding member according to claim 4, characterized in that: The hard particle powder further contains Sn.

6. The method for manufacturing a sliding member according to claim 5, characterized in that: The hard particle powder contains 1 mass % or more of Sn.

7. The method for manufacturing a sliding member according to any one of claims 4 to 6, characterized in that: When the entire mixed powder is taken as 100 mass %, the blending amount of the hard particle powder is 1 to 40 mass %.

8. The method for manufacturing a sliding member according to any one of claims 4 to 6, characterized in that: The mixed powder further includes a second powder containing Cu, Co, Fe, Ni, Si and Cr.

9. The method for manufacturing a sliding member according to claim 8, characterized in that: The second powder further contains Sn.

10. The method for manufacturing a sliding member according to claim 9, characterized in that: The second powder contains 1 mass % or more of Sn.

11. The method for manufacturing a sliding member according to claim 8, characterized in that: When the entire mixed powder is taken as 100 mass %, the blending amount of the second powder is 2 to 38 mass %.

12. The method for manufacturing a sliding member according to claim 8, characterized in that: When the entire mixed powder is assumed to be 100% by mass, the blending amount of the hard particle powder is 1 to 40% by mass, and the blending amount of the second powder is 2 to 38% by mass.

13. The method for manufacturing a sliding member according to any one of claims 4 to 6, characterized in that: The first powder further contains P.

14. The method for manufacturing a sliding member according to any one of claims 4 to 6, characterized in that: When the entire hard particle powder is set to 100 mass%, the content of each constituent element in the hard particle powder is Si: 3-7 mass%, Fe: 2-16 mass%, Mo: 24-28 mass%, Co: 14-20 mass%, Cr: 1-10 mass%, Sn: 1-15 mass%, and Cu: balance.

15. The method for manufacturing a sliding member according to claim 8, characterized in that: When the second powder as a whole is set to 100 mass%, the content of each constituent element in the second powder is Co: 0.6~4.6 mass%, Fe: 1.6~5.6 mass%, Ni: 10~14 mass%, Si: 0.5~4.5 mass%, Cr: 0.5~1.5 mass%, Sn: 1~15 mass%, Cu: balance.

16. A method for manufacturing a bearing, characterized in that: have: A step of spreading a mixed powder on one surface of a metal substrate, the mixed powder comprising a first powder containing Cu, Sn and Bi and a hard particle powder containing a Laves phase composed of a composition of Co, Mo and Si, the hard particle powder containing Cu, Si, Fe, Mo, Co and Cr; The mixed powder dispersed on the metal substrate is sintered at 800-900° C. to form a sliding layer; a step of rolling the metal substrate on which the sliding layer is formed; and A step of processing the rolled metal base material into a rolled bushing shape with the sliding layer as an inner side.

17. The method for manufacturing a bearing according to claim 16, characterized in that: When the entire hard particle powder is set to 100 mass%, the content of each constituent element in the hard particle powder is Si: 3-7 mass%, Fe: 2-16 mass%, Mo: 24-28 mass%, Co: 14-20 mass%, Cr: 1-10 mass%, Sn: 1-15 mass%, and Cu: balance.

18. The method for manufacturing a bearing according to claim 16 or 17, characterized in that: The mixed powder further includes a second powder containing Cu, Co, Fe, Ni, Si and Cr.

19. The method for manufacturing a bearing according to claim 18, characterized in that: When the second powder as a whole is set to 100 mass%, the content of each constituent element in the second powder is Co: 0.6~4.6 mass%, Fe: 1.6~5.6 mass%, Ni: 10~14 mass%, Si: 0.5~4.5 mass%, Cr: 0.5~1.5 mass%, Sn: 1~15 mass%, Cu: balance.

20. A mixed powder for sliding surfaces of sliding members and bearings, characterized in that: Include: a first powder comprising Cu and Sn; A hard particle powder containing a Laves phase composed of Co, Mo, and Si and further containing 1 mass % or more of Sn; and A second powder containing Cu, Co, Fe, Ni, Si, and Cr, and further containing 1 mass % or more of Sn.

21. The mixed powder for sliding surfaces of sliding members and bearings according to claim 20, characterized in that: When the entire hard particle powder is set to 100 mass%, the content of each constituent element in the hard particle powder is Si: 3-7 mass%, Fe: 2-16 mass%, Mo: 24-28 mass%, Co: 14-20 mass%, Cr: 1-10 mass%, Sn: 1-15 mass%, and Cu: balance.

22. The mixed powder for sliding surfaces of sliding members and bearings according to claim 20 or 21, characterized in that: When the second powder as a whole is set to 100 mass%, the content of each constituent element in the second powder is Co: 0.6~4.6 mass%, Fe: 1.6~5.6 mass%, Ni: 10~14 mass%, Si: 0.5~4.5 mass%, Cr: 0.5~1.5 mass%, Sn: 1~15 mass%, Cu: balance.

23. A hard particle powder for a sliding surface of a bearing, comprising a Laves phase composed of Co, Mo and Si, and further comprising 1 mass % or more of Sn, When the entire hard particle powder is set to 100 mass%, the content of each constituent element in the hard particle powder for the sliding surface of the bearing is Si: 3-7 mass%, Fe: 2-16 mass%, Mo: 24-28 mass%, Co: 14-20 mass%, Cr: 1-10 mass%, Sn: 1-15 mass%, Cu: balance.

24. A hard particle powder for sliding surfaces of sliding members and bearings, characterized in that: Contains a Laves phase composed of Co, Mo and Si, When the entire hard particle powder is taken as 100 mass%, Co: 14-20 mass%, Mo: 24-28 mass%, Si: 3-7 mass%, Fe: 2-16 mass%, Cr: 1-10 mass%, Sn: 4 mass% or more, and Cu: the balance.

Citation Information

Patent Citations

  • Copper-based sliding material and its manufacturing method

    JP2005163074A

  • Sliding material and method for its manufacture

    JP2008050688A

  • High-hardness hardfacing alloy powder

    CN102773627A

  • Copper alloy, use of a copper alloy, bearing having a copper alloy, and method for producing a bearing composed of a copper alloy

    CN105209646A

  • Slide member and method for manufacturing same

    CN109790598A